PENGARUH PEMBERIAN KOSENTRASI AIR CUCIAN BERAS TERHADAP PRODUKSI PARE (Momordica charantia L.) - Katarina, Silvia - (STKIP PGRI Sumbar, 2014)
Pare (Momordica charantica L.) is a creep and spread plant which has fruit advantage to increaseeating desire, accelerate assimilation, can cure yellow disease, impotence, wasir, infertility for woman,increase ASI production and antiseptic. The problem which is faced in cultivation of pare is not reachingthe maximum production. To solve this, so that it need body controller substance, that is rice washingwater. This water consist of BI vitamin, carbohydrate, phosphore, nitrogen and iron substance. Thewashing water can enrich hara element which is in soil and able to fix phisyc and biology character so thatit can be hoped to be able to increase pare production result (Momordica charantica L.). This research hasbeen done in May until July 2014 in Dusun Sirandah, Kenagarian Lakitan, Kecamatan Lengayang,Kabupaten Pesisir Selatan. This research use Complete Random Design (RAL) which is consist of 5 actand 4 replecation. The treatment which are : given treatment A control (give usual water), treatment Bgive rice washing water with 25% concentrations treatment C with 50% concentrations treatment D with75% concentrations and treatment E with 100% concentrations. The data analysis which is used iscontinues examination by testing DNMRT in level 5%. The result of the research show that giving ricewashing water can influence quantities of pare fruit. The most quantities is in treatment E with giving ricewashing water 100%, that is 3 fruits. But, giving water didnât give influence to weight of pare(Momordica charantica L.)